2021
DOI: 10.3389/fcell.2021.746145
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Patterns in CD8+ T Cells Discern Psoriasis From Psoriatic Arthritis and Correlate With Cutaneous Disease Activity

Abstract: Background: Psoriasis is a T cell-mediated chronic autoimmune/inflammatory disease. While some patients experience disease limited to the skin (skin psoriasis), others develop joint involvement (psoriatic arthritis; PsA). In the absence of disease- and/or outcome-specific biomarkers, and as arthritis can precede skin manifestations, diagnostic and therapeutic delays are common and contribute to disease burden and damage accrual.Objective: Altered epigenetic marks, including DNA methylation, contribute to effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…As a limitation of this study, because of the nature of the cohort, we are unable to separate specific cell populations and measure the extent to which the methylation changes identified might be affected by different cellular compositions between patients. However, a recent study (25) found no significant differences in the proportions of CD8+ T cell subpopulations (naïve, effector memory, central memory, and effector memory cells re‐expressing CD45RA) between cutaneous psoriasis and PsA, suggesting that the effect of these cell subpopulations is not as marked in PsA as in other diseases.…”
Section: Discussionmentioning
confidence: 93%
“…As a limitation of this study, because of the nature of the cohort, we are unable to separate specific cell populations and measure the extent to which the methylation changes identified might be affected by different cellular compositions between patients. However, a recent study (25) found no significant differences in the proportions of CD8+ T cell subpopulations (naïve, effector memory, central memory, and effector memory cells re‐expressing CD45RA) between cutaneous psoriasis and PsA, suggesting that the effect of these cell subpopulations is not as marked in PsA as in other diseases.…”
Section: Discussionmentioning
confidence: 93%
“…It is characterized by increased keratinocyte proliferation and immune cell infiltration of the skin, including T lymphocytes. Effector CD4 + and CD8 + T cells centrally contribute to skin inflammation and tissue damage in psoriasis [12,13]. As in SLE, the molecular pathophysiology of psoriasis is incompletely understood.…”
Section: Immune Dysregulation In Systemic Autoimmune/ Inflammatory Di...mentioning
confidence: 99%
“…Increased methylation of the PDCD1 gene results in reduced expression of the regulatory co‐receptor PD‐1 on CD4 + T cells [18]. Reduced methylation of the IFNG promoter in DN T cells allows for IFN‐γ expression [48], and distinct DNA methylation patterns in CD8 + T cells allow distinguishing between patients with skin psoriasis, psoriatic arthritis and healthy individuals [13].…”
Section: Transcriptional and Epigenetic Regulation Of Effector T Cellsmentioning
confidence: 99%
“…However, leakage of immune deregulation from the skin to the joint is suspected 73 , potentially involving lymphocyte subsets such as CD8 + T effector memory CD45RA cells 74 and CD8 + CCR10 + T cells 75 . DNA methylation patterns of CD8 + T cells can differentiate patients with psoriasis from those with PsA, suggesting the potential for early patient stratification for therapy 76 . Another comorbidity in adult chronic arthritis is an increased cardiovascular risk.…”
Section: A ‘Critical Window In (Epi)genetics’mentioning
confidence: 99%